Tekstur, Kadar β-Karoten dan Kalsium Flakes dengan Formulasi Tepung Labu Kuning dan Daun Kelor - Tiurma Wiliana Susanti Panjaitan; Dwi Agustiyah Rosida (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2021)
Flakes can be made from various food ingredients that contain carbohydrates and can be added to other nutritional sources to meet nutritional needs. Therefore, it is important to create cereal products that meet the criteria as alternative foods rich in energy, protein and other nutrients such as calcium (Ca). Yellow squash contains β- carotene while moringa plants, especially in leaves, contain high levels of calcium. The study aims to determine the Ca content and texture of the flakes substituted with pumpkin flour and moringa leaf flour. Substitution with pumpkin and moringa leaves is expected to meet the need for β-carotene and calcium. This research is an experimental study using a completely randomized design with one factor, namely the formulation of pumpkin flour and moringa leaf flour to substitute wheat flour with the composition of F0 (100: 0: 0), F1 (70: 27,5: 2,5), F2 (70: 25: 5) and F3 (70: 22,5: 7,5). The parameters observed were β-carotene levels, calcium levels and physical / texture properties were analyzed by analysis of variance (ANOVA) and the least significant difference (LSD) if there was a difference at the 5% real level. The results showed that the flour formulation of pumpkin and moringa leaf had no effect on the flake texture but significantly affected calcium and β-carotene levels. The more the addition of moringa leaf flour and the less pumpkin flour, the higher the calcium level. Conversely, the more pumpkin flour added, and the more moringa leaf flour reduced, the higher the β-carotene content. Based on the β-carotene content, the recommended formula is F1 because it produces the highest β-carotene content, while the F3 formulation produces the highest calcium content. Keywords: flake, pumpkin flour, moringa leaf flour, β-carotene, calcium content, texture